Statistical analysis of fatigue crack propagation data of materials from ancient portuguese metallic bridges (Fracture and Structural Integrity, 2017)
In Portugal there is a number of old metallic riveted railway and highway bridges that were erected by the end of the 19th century and beginning of the 20th century, and are still in operation, requiring inspections and remediation measures to overcome fatigue damage. Residual fatigue life predictions should be based on actual fatigue data from bridge materials which is scarce due to the material specificities. Fatigue crack propagation data of materials from representative Portuguese riveted bridges, namely the Pinhão and Luiz I road bridges, the Viana road/railway bridge, the Fão road bridge and the Trezói railway bridge were considered in this study. The fatigue crack growth rates were correlated using the Paris’s law. Also, a statistical analysis of the pure mode I fatigue crack growth (FCG) data available for the materials from the ancient riveted metallic bridges is presented. Based on this analysis, design FCG curves are proposed and compared with BS7910 standard proposal, for the Paris region, which is one important fatigue regime concerning the application of the Fracture Mechanics approaches, to predict the remnant fatigue life of structural details.
Keywords: Fracture Mechanics; Fatigue Crack Growth; Statistical Analysis; Old Steels; Ancient Bridges; BS7910